Rancangan Kurikulum Sekolah Minggu bagi anak Usia 7 Tahun di Sinode Gereja Bethel Tabernakel - Ragil Kristiawan; David Priyo Susilo; Gregorius Suwito; Willyanto Pontonuwu; Tri Astuti (Sabda: Jurnal Teologi Kristen, 2025)
The curriculum is a vital part of the implementation of Sunday school. The GBT Synod understands this so they plan to create a curriculum that can be used nationally. As a concrete step, the GBT Synod collaborated with STT KAO to produce Sunday school curriculum teaching for 7-year-old children. What is the right curriculum design for 7-year-old Sunday schoolchildren at the GBT Synod? By using this type of qualitative research, literature studies are obtained several important things to answer this question. Some aspects that need to be considered in making this curriculum include: the urgency of the curriculum itself, the characteristics of 7-year-old Sunday school children, and the spirituality of Sunday school children at the age of 7. As a result, several things can be mentioned in this curriculum. First, the curriculum is set in a span of one year. Second, the content in the curriculum must pay attention to the themes that have been the dogma of GBT. Third, the content of the curriculum must also pay attention to the ecclesiastical calendars. Finally, 7-year-old Sunday schoolchildren are equipped with the creation stories in the Bible as the basis for an introduction to Christian doctrine.Abstrak:Kurikulum menjadi bagian yang vital dalam penyelenggaraan sekolah minggu. Sinode GBT memahami akan hal ini sehingga mereka merencanakan adanya pembuatan kurikulum yang dapat dipakai secara nasional. sebagai langkah konkritnya, Sinode GBT bekerjasama dengan STT KAO untuk menghasilkan pengajaran kurikulum sekolah minggu bagi anak usia 7 tahun. Bagaimanakah rancangan kurikulum yang tepat bagi anak sekolah minggu usia 7 tahun di Sinode GBT? Dengan menggunakan jenis penelitian kualitatif studi pustaka didapatkan beberapa hal penting untuk menjawab pertanyaan ini. Beberapa aspek yang perlu dipertimbangkan dalam pembuatan kurikulum ini diantaranya: urgensi dari kurikulum itu sendiri, karakteristik anak sekolah minggu usia 7 tahun, serta kerohanian anak sekolah minggu di usia 7 tahun. Sebagai hasilnya, beberapa hal dapat disebutkan dalam kurikulum ini. Pertama, kurikulum ditetapkan dalam rentang satu tahun. Kedua, Isi dalam kurikulum harus memperhatikan tema-tema yang selama ini menjadi dogma GBT. Ketiga, isi kurikulum juga harus memperhatikan kalender-kalender gerejani. Terakhir, anak sekolah minggu usia 7 tahun dibekali dengan cerita-cerita penciptaan dalam Alkitab sebagai dasar pengenalan doktrin Kristen. Kata Kunci: Kurikulum Sekolah Minggu, Anak 7 Tahun, Sinode GBT